A COMPARATIVE STUDY ON THE EFFECT OF GENERAL ANAESTHESIA ON BLOOD GLUCOSE LEVELS IN NON-DIABETIC AND CONTROLLED DIABETIC PATIENTS: AN OBSERVATIONAL STUDY AT S. M. S. MEDICAL COLLEGE, JAIPUR - SHARMA, RAJEEV; SINGH, AJAY; CHHIPA, SANDEEP (International Journal of Current Pharmaceutical Research, 2024)
Objective: Diabetes, a complex metabolic disorder, poses significant challenges during surgery due to its association with chronic hyperglycemia. Surgical stress triggers hormonal changes, impacting glucose homeostasis. With an increasing global prevalence of diabetes, understanding the interplay between surgery, stress, and diabetes becomes crucial for perioperative management. Methods: This hospital-based cross-sectional observational study included 222 patients (111 non-diabetic and 111 controlled diabetic) undergoing elective surgery. Demographic data, hemodynamic parameters, and blood glucose levels were assessed at various intervals. Statistical analyses compared age, gender, blood glucose levels, and hemodynamic responses between the two groups. Results: Demographic parameters were comparable between non-diabetic and controlled diabetic groups. Hemodynamic responses, including heart rate and blood pressure, showed no significant differences during the surgery. Blood glucose levels were similar preoperatively and up to 30 min post-intubation. However, a significant difference was observed after 5 min of extubation, with controlled diabetic patients exhibiting higher levels. Variations in blood glucose levels after extubation were statistically significant, emphasizing the importance of postoperative monitoring. Conclusion: This study highlights the intricate relationship between surgery, stress, and diabetes, emphasizing the need for tailored perioperative management. Close monitoring, especially during critical moments, is essential to ensure optimal glucose control and mitigate complications. The findings align with existing literature, reinforcing the importance of individualized approaches for diabetic patients undergoing surgery.